A kind of acid corrosion resistant insulating synthetic mica coating substrate and preparation method thereof

By using synthetic mica powder, epoxy resin and other raw materials in the coated substrate, combined with the synergistic effect of coupling double-double adjuster and nano-silicon carbide modifier, the poor insulation performance and protection of existing coating substrates are solved. The problems of poor self-cleaning properties of dirty and insufficient acid and corrosion resistance have achieved significant improvements in insulation, anti-fouling and self-cleaning properties and acid and corrosion resistance.

CN118325425BActive Publication Date: 2025-02-07GUANGDONG SANBAO NEW MATERIALS TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410501997.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-25
Publication Date
2025-02-07
Estimated Expiration
2044-04-25

AI Technical Summary

Technical Problem

The poor insulation performance, poor anti-fouling self-cleaning properties and insufficient acid and corrosion resistance of existing coating substrates limit the efficiency of the product.

Method used

Using synthetic mica powder, epoxy resin, curing agent, polydimethylsiloxane and benzoin, combined with coupling effect double-drug and nano-silicon carbide modifier, the particle size is 400 objects by wet crushing and grinding process. Mica powder is synthesized and heat treatment and ultrasonic modification are carried out to form an acid-resistant insulated synthetic mica coating substrate.

Benefits of technology

The coordinated improvement of insulation and anti-fouling self-cleaning performance has been achieved, and the acid and corrosion resistance of the product has been significantly improved, and the efficiency of the product has been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004808967070000141
    Figure BDA0004808967070000141
  • Figure BDA0004808967070000161
    Figure BDA0004808967070000161
Patent Text Reader

Abstract

The present invention relates to the technical field of synthetic mica coatings, and specifically discloses an acid-corrosion-resistant insulating synthetic mica coating substrate and a preparation method thereof. The coating substrate comprises the following raw materials in parts by weight: 15 to 20 parts of synthetic mica powder, 8 to 14 parts of coupling-effect double-adjusting agents, 4 to 7 parts of nano-silicon carbide modifiers, 30 to 40 parts of epoxy resins, 6 to 9 parts of curing agents, 2 to 4 parts of polydimethylsiloxanes, and 0.5 to 1.0 parts of benzoin. The coating substrate of the present invention adopts synthetic mica powder and nano-silicon carbide modifiers. The synthetic mica powder has excellent acid-corrosion resistance and insulation. By blending epoxy resin, curing agent, polydimethylsiloxane, and benzoin, and then combining coupling-effect double-adjusting agents and nano-silicon carbide modifiers, the two are coordinated with each other to form the coating substrate raw material in coordination. The obtained product can achieve coordinated improvement of insulation, anti-fouling and self-cleaning performance, and the acid-corrosion resistance and stability of the product are remarkable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of mica coatings, and in particular to an acid corrosion resistant insulating synthetic mica coating substrate and a preparation method thereof. Background Art

[0002] Synthetic mica powder is a kind of artificial synthetic mica powder that has been wet-grinded. Generally, mechanical grinding, hydraulic crushing and other methods are used to grind the artificial synthetic mica powder into micro-nano particles. Due to its very small particle size, it has many excellent properties and application characteristics, with very small particle size and high surface activity.

[0003] The existing coating base is made of powder coating, and the product has poor insulation performance. In order to improve the insulation of the product, it is easy to cause the product's anti-fouling and self-cleaning properties to be poor. The insulation and anti-fouling and self-cleaning properties of the product are difficult to improve in a coordinated manner, and the product's acid corrosion resistance is poor, which limits the product's use efficiency. Based on this, the present invention further improves it. Summary of the invention

[0004] In view of the defects of the prior art, the purpose of the present invention is to provide an acid corrosion resistant insulating synthetic mica coating substrate and a preparation method thereof to solve the problems raised in the above background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution:

[0006] The present invention provides an acid-corrosion-resistant insulating synthetic mica coating substrate, which comprises the following raw materials in parts by weight:

[0007] 15-20 parts of synthetic mica powder, 8-14 parts of coupling effect double adjuster, 4-7 parts of nano silicon carbide modifier, 30-40 parts of epoxy resin, 6-9 parts of curing agent, 2-4 parts of polydimethylsiloxane, 0.5-1.0 parts of benzoin;

[0008] Synthetic mica powder is made by wet crushing and grinding process:

[0009] The synthetic mica fragments are sorted and soaked, crushed by 4.0-7.0MPa high-pressure water impact, dehydrated, crushed by a wheel mill with a gap of 0.8-1mm, classified and dried to obtain synthetic mica powder with a particle size of 400 meshes.

[0010] Preferably, the epoxy resin is a phenolic modified epoxy resin, the epoxy value is 0.12 to 0.135 eq / 100 g, and the softening point is 110 to 120° C.; the curing agent is a phenolic curing agent, and the phenolic curing agent is p-diphenol.

[0011] Preferably, the preparation method of the coupling effect double regulator is:

[0012] The specific preparation method is:

[0013] S1: first heat-treat the flaky talc at 310-320°C for 10-15 min, then reduce the temperature to 175-185°C at a rate of 2-5°C / min, keep the temperature for 5-10 min, and finally reduce the temperature to 55°C at a rate of 1-3°C / min, and keep the temperature;

[0014] S2: Preparation of coupling liquid;

[0015] The specific preparation method is:

[0016] S01: First, the nano-hydroxyapatite is stirred and mixed in a sufficient amount of 10% by mass potassium permanganate solution, and then washed with water and dried;

[0017] S02: ball milling the dried nano-hydroxyapatite and the effector according to a weight ratio of 5:3, with a ball milling speed of 1000-1500 r / min for 1-2 hours. After the ball milling is completed, washing and drying are performed to obtain the effector adjusted by the nano-hydroxyapatite;

[0018] S03: Preparation of continuous adjustment solution;

[0019] The preparation method of the continuous adjustment solution is:

[0020] 4-7 parts of silane coupling agent KH560, 1-3 parts of chitosan solution, 6-10 parts of sodium lignin sulfonate solution and 3-5 parts of ethanol solvent are mixed to obtain a continuous adjustment solution;

[0021] S04: the nano-hydroxyapatite-adjusted effect agent and the coupling liquid are mixed thoroughly in a weight ratio of 2:5 to obtain a coupling effect liquid;

[0022] S3: subjecting the heat-insulated flaky talc powder and the coupling liquid to ultrasonic modification treatment in a weight ratio of 2:(5-7), washing with water and drying after the ultrasonic treatment.

[0023] Preferably, the ultrasonic power of the S3 ultrasonic modification treatment is 350-400 W, and the ultrasonic time is 20-30 min.

[0024] Preferably, the mass fraction of the chitosan solution in the S03 is 4-7%; the mass fraction of the sodium lignin sulfonate solution is 10-15%.

[0025] Preferably, the preparation method of the enhancement agent is:

[0026] 1-3 parts of nano-silica sol and 3-4 parts of sodium dodecylbenzene sulfonate are added to 5-8 parts of 5% by mass yttrium nitrate solution, and then 2-3 parts of wollastonite and 1-2 parts of sodium citrate solution are added and stirred to obtain an effective agent.

[0027] Preferably, the mass fraction of the sodium citrate solution is 10-15%.

[0028] Preferably, the preparation method of the nano silicon carbide modifier is:

[0029] S101: placing the nano-silicon carbide in a proton irradiation box for irradiation for 20 to 30 minutes, with an irradiation power of 350 to 400 W, and obtaining a nano-irradiated silicon carbide agent after the irradiation is completed;

[0030] S102: 4 to 7 parts of nano-irradiated silicon carbide agent, 1 to 3 parts of tetrabutyl titanate, 1 to 2 parts of urea and 6 to 10 parts of lanthanum chloride solution are mixed and ball-milled at a speed of 1000 to 1500 r / min for 1 to 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a nano-silicon carbide modifier.

[0031] Preferably, the mass fraction of the lanthanum chloride solution is 2-5%.

[0032] The present invention also provides a method for preparing an acid corrosion resistant insulating synthetic mica coating substrate, comprising the following steps:

[0033] The raw materials are weighed according to the ratio; then the raw materials are sent to a mixer and mixed thoroughly, and then extruded in a twin-screw extruder at an extrusion temperature of 120° C., and then cooled to obtain a sheet material, and finally ground to a particle size of 400 meshes to obtain the acid-corrosion-resistant insulating synthetic mica coating substrate of the present invention.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] 1. The coating substrate of the present invention adopts synthetic mica powder in combination with epoxy resin, curing agent, polydimethylsiloxane and benzoin raw materials. The synthetic mica powder has excellent acid corrosion resistance and insulation. It is combined with a coupling effect double adjuster and a nano silicon carbide modifier. The two are coordinated with each other to form the coating substrate raw material. The obtained product can achieve coordinated improvement in insulation, anti-fouling and self-cleaning performance, and the acid corrosion resistance and stability of the product are remarkable.

[0036] 2. The flaky talc is heat treated at 310-320°C for 10-15 minutes, then reduced to 175-185°C at a rate of 2-5°C / min, kept warm for 5-10 minutes, and finally reduced to 55°C at a rate of 1-3°C / min. The flaky activity and dispersion of the flaky talc are optimized by continuous heat treatment, so that the raw materials are better distributed in the system. The interfacial compatibility between the flaky talc and the raw materials is optimized by ultrasonic modification with coupling effect liquid, the interfacial effect of the flaky talc is improved, and the performance of the product is optimized. At the same time, the flaky talc is interspersed in the system with synthetic mica, and the acid corrosion resistance and insulation of the product are further improved.

[0037] 3. The coupling liquid uses nano-hydroxyapatite treated with potassium permanganate solution to optimize the activity and dispersion of nano-hydroxyapatite, and then improves it through ball milling with an effect agent. In the preparation of the effect agent, nano-silica sol, sodium dodecylbenzene sulfonate, yttrium nitrate solution, wollastonite and sodium citrate solution are mixed and coordinated. Through the mutual coordination and synergy between the raw materials, the needle-like structure of wollastonite is matched with hydroxyapatite, and the point-like hydroxyapatite distribution system is matched with the needle-like structure of wollastonite. Then, the flake talcum powder flake distribution system is used as a carrier. Through the mutual coordination and synergy between the raw materials, self-cleaning points and interlaced distribution system structure can be formed, thereby enhancing the insulation and self-cleaning coordination of the product and improving the acid corrosion resistance and stability of the product.

[0038] 4. The continuous adjustment liquid obtained by blending silane coupling agent KH560, chitosan solution, sodium lignin sulfonate solution and ethanol solvent is synergistically formulated with the effect agent adjusted by nano-hydroxyapatite. The silane coupling agent KH560 is used as an interface agent to achieve the connection between inorganic and organic raw materials. The coupling effect liquid obtained by blending chitosan solution, sodium lignin sulfonate solution and ethanol solvent can further optimize the interface and active performance of the product raw materials, thereby further improving the product performance;

[0039] 5. The active agent is made of nano-silicon carbide and treated with proton irradiation to optimize the activity performance of nano-silicon carbide. It is then mixed with tetrabutyl titanate, urea and lanthanum chloride solution and ball milled. The ball milling is improved by co-matching between the raw materials. The obtained active agent and the coupling agent are further coordinated and synergistic, thereby further improving the performance of the product. DETAILED DESCRIPTION

[0040] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] The present embodiment provides an acid-corrosion-resistant insulating synthetic mica coating substrate, the coating substrate comprising the following raw materials in parts by weight:

[0042] 15-20 parts of synthetic mica powder, 8-14 parts of coupling effect double adjuster, 4-7 parts of nano silicon carbide modifier, 30-40 parts of epoxy resin, 6-9 parts of curing agent, 2-4 parts of polydimethylsiloxane, 0.5-1.0 parts of benzoin;

[0043] Synthetic mica powder is made by wet crushing and grinding process:

[0044] The synthetic mica fragments are sorted and soaked, crushed by 4.0-7.0MPa high-pressure water impact, dehydrated, crushed by a wheel mill with a gap of 0.8-1mm, classified and dried to obtain synthetic mica powder with a particle size of 400 meshes.

[0045] The epoxy resin in this embodiment is a phenolic modified epoxy resin, the epoxy value is 0.12-0.135eq / 100g, and the softening point is 110-120°C; the curing agent is a phenolic curing agent, and the phenolic curing agent is p-diphenol.

[0046] The preparation method of the coupling effect double regulator of this embodiment is:

[0047] The specific preparation method is:

[0048] S1: first heat-treat the flaky talc at 310-320°C for 10-15 min, then reduce the temperature to 175-185°C at a rate of 2-5°C / min, keep the temperature for 5-10 min, and finally reduce the temperature to 55°C at a rate of 1-3°C / min, and keep the temperature;

[0049] S2: Preparation of coupling liquid;

[0050] The specific preparation method is:

[0051] S01: First, the nano-hydroxyapatite is stirred and mixed in a sufficient amount of 10% by mass potassium permanganate solution, and then washed with water and dried;

[0052] S02: ball milling the dried nano-hydroxyapatite and the effector according to a weight ratio of 5:3, with a ball milling speed of 1000-1500 r / min for 1-2 hours. After the ball milling is completed, washing and drying are performed to obtain the effector adjusted by the nano-hydroxyapatite;

[0053] S03: Preparation of continuous adjustment solution;

[0054] The preparation method of the continuous adjustment solution is:

[0055] 4-7 parts of silane coupling agent KH560, 1-3 parts of chitosan solution, 6-10 parts of sodium lignin sulfonate solution and 3-5 parts of ethanol solvent are mixed to obtain a continuous adjustment solution;

[0056] S04: the nano-hydroxyapatite-adjusted effect agent and the coupling liquid are mixed thoroughly in a weight ratio of 2:5 to obtain a coupling effect liquid;

[0057] S3: subjecting the heat-insulated flaky talc powder and the coupling liquid to ultrasonic modification treatment in a weight ratio of 2:(5-7), washing with water and drying after the ultrasonic treatment.

[0058] The ultrasonic power of the S3 ultrasonic modification treatment in this embodiment is 350-400 W, and the ultrasonic time is 20-30 min.

[0059] The mass fraction of the chitosan solution in S03 of this embodiment is 4-7%; the mass fraction of the sodium lignin sulfonate solution is 10-15%.

[0060] The preparation method of the effect-enhancing agent of the present embodiment is:

[0061] 1-3 parts of nano-silica sol and 3-4 parts of sodium dodecylbenzene sulfonate are added to 5-8 parts of 5% by mass yttrium nitrate solution, and then 2-3 parts of wollastonite and 1-2 parts of sodium citrate solution are added and stirred to obtain an effective agent.

[0062] The mass fraction of the sodium citrate solution in this embodiment is 10-15%.

[0063] The preparation method of the nano silicon carbide modifier of this embodiment is:

[0064] S101: placing the nano-silicon carbide in a proton irradiation box for irradiation for 20 to 30 minutes, with an irradiation power of 350 to 400 W, and obtaining a nano-irradiated silicon carbide agent after the irradiation is completed;

[0065] S102: 4 to 7 parts of nano-irradiated silicon carbide agent, 1 to 3 parts of tetrabutyl titanate, 1 to 2 parts of urea and 6 to 10 parts of lanthanum chloride solution are mixed and ball-milled at a speed of 1000 to 1500 r / min for 1 to 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a nano-silicon carbide modifier.

[0066] The mass fraction of the lanthanum chloride solution in this embodiment is 2-5%.

[0067] A method for preparing an acid corrosion resistant insulating synthetic mica coating substrate according to the present embodiment comprises the following steps:

[0068] The raw materials are weighed according to the ratio; then the raw materials are sent to a mixer and mixed thoroughly, and then extruded in a twin-screw extruder at an extrusion temperature of 120° C., and then cooled to obtain a sheet material, and finally ground to a particle size of 400 meshes to obtain the acid-corrosion-resistant insulating synthetic mica coating substrate of the present invention.

[0069] Example 1.

[0070] The present embodiment provides an acid-corrosion-resistant insulating synthetic mica coating substrate, the coating substrate comprising the following raw materials in parts by weight:

[0071] 15 parts of synthetic mica powder, 8 parts of coupling effect double adjuster, 4 parts of nano silicon carbide modifier, 30 parts of epoxy resin, 6 parts of curing agent, 2 parts of polydimethylsiloxane, 0.5 parts of benzoin;

[0072] Synthetic mica powder is made by wet crushing and grinding process:

[0073] The synthetic mica fragments were sorted and soaked, crushed by 4.0MPa high-pressure water impact, dehydrated, crushed by a wheel mill with a gap of 0.8mm, classified and dried to obtain synthetic mica powder with a particle size of 400 mesh.

[0074] The epoxy resin in this embodiment is a phenolic modified epoxy resin, the epoxy value is 0.12eq / 100g, and the softening point is 110°C; the curing agent is a phenolic curing agent, and the phenolic curing agent is p-diphenol.

[0075] The preparation method of the coupling effect double regulator of this embodiment is:

[0076] The specific preparation method is:

[0077] S1: The flaky talc was first heat treated at 310°C for 10 min, then the temperature was reduced to 175°C at a rate of 2°C / min, and kept at this temperature for 5 min, and finally the temperature was reduced to 55°C at a rate of 1°C / min and kept at this temperature;

[0078] S2: Preparation of coupling liquid;

[0079] The specific preparation method is:

[0080] S01: First, the nano-hydroxyapatite is stirred and mixed in a sufficient amount of 10% by mass potassium permanganate solution, and then washed with water and dried;

[0081] S02: ball milling the dried nano-hydroxyapatite and the effector according to a weight ratio of 5:3, with a ball milling speed of 1000r / min for 1h. After the ball milling is completed, washing and drying are performed to obtain the effector adjusted by the nano-hydroxyapatite;

[0082] S03: Preparation of continuous adjustment solution;

[0083] The preparation method of the continuous adjustment solution is:

[0084] 4 parts of silane coupling agent KH560, 1 part of chitosan solution, 6 parts of sodium lignin sulfonate solution and 3 parts of ethanol solvent were mixed to obtain a continuous adjustment solution;

[0085] S04: the nano-hydroxyapatite-adjusted effect agent and the coupling liquid are mixed thoroughly in a weight ratio of 2:5 to obtain a coupling effect liquid;

[0086] S3: subjecting the heat-insulated flaky talcum powder and the coupling liquid to ultrasonic modification treatment in a weight ratio of 2:5, washing with water and drying after the ultrasonic modification.

[0087] The ultrasonic power of S3 in the ultrasonic modification treatment of this embodiment is 350W, and the ultrasonic time is 20min.

[0088] The mass fraction of the chitosan solution in S03 of this embodiment is 4%; the mass fraction of the sodium lignin sulfonate solution is 10%.

[0089] The preparation method of the effect-enhancing agent of the present embodiment is:

[0090] One part of nano-silica sol and three parts of sodium dodecylbenzene sulfonate were added into five parts of 5% by mass yttrium nitrate solution, and then two parts of wollastonite and one part of sodium citrate solution were added and stirred thoroughly to obtain an enhancer.

[0091] The mass fraction of the sodium citrate solution in this embodiment is 10%.

[0092] The preparation method of the nano silicon carbide modifier of this embodiment is:

[0093] S101: placing the nano-silicon carbide in a proton irradiation box for 20 minutes, with an irradiation power of 350W, and obtaining a nano-irradiated silicon carbide agent after the irradiation is completed;

[0094] S102: 4 parts of nano-irradiated silicon carbide agent, 1 part of tetrabutyl titanate, 1 part of urea and 6 parts of lanthanum chloride solution are mixed and ball-milled at a ball-milling speed of 1000 r / min for 1 hour. After the ball-milling is completed, the mixture is washed with water and dried to obtain a nano-silicon carbide modifier.

[0095] The mass fraction of the lanthanum chloride solution in this embodiment is 2%.

[0096] A method for preparing an acid corrosion resistant insulating synthetic mica coating substrate according to the present embodiment comprises the following steps:

[0097] The raw materials are weighed according to the ratio; then the raw materials are sent to a mixer and mixed thoroughly, and then extruded in a twin-screw extruder at an extrusion temperature of 120° C., and then cooled to obtain a sheet material, and finally ground to a particle size of 400 meshes to obtain the acid-corrosion-resistant insulating synthetic mica coating substrate of the present invention.

[0098] Example 2.

[0099] The present embodiment provides an acid-corrosion-resistant insulating synthetic mica coating substrate, the coating substrate comprising the following raw materials in parts by weight:

[0100] 20 parts of synthetic mica powder, 14 parts of coupling effect double adjuster, 7 parts of nano silicon carbide modifier, 40 parts of epoxy resin, 9 parts of curing agent, 4 parts of polydimethylsiloxane, 1.0 part of benzoin;

[0101] Synthetic mica powder is made by wet crushing and grinding process:

[0102] The synthetic mica fragments were sorted and soaked, crushed by 7.0MPa high-pressure water impact, dehydrated, crushed by a wheel mill with a gap of 1mm, classified and dried to obtain synthetic mica powder with a particle size of 400 mesh.

[0103] The epoxy resin in this embodiment is a phenolic modified epoxy resin, the epoxy value is 0.135eq / 100g, and the softening point is 120°C; the curing agent is a phenolic curing agent, and the phenolic curing agent is p-diphenol.

[0104] The preparation method of the coupling effect double regulator of this embodiment is:

[0105] The specific preparation method is:

[0106] S1: The flaky talc was first heat treated at 320°C for 15 min, then the temperature was reduced to 185°C at a rate of 5°C / min, and kept at this temperature for 10 min, and finally the temperature was reduced to 55°C at a rate of 3°C / min, and kept at this temperature;

[0107] S2: Preparation of coupling liquid;

[0108] The specific preparation method is:

[0109] S01: First, the nano-hydroxyapatite is stirred and mixed in a sufficient amount of 10% by mass potassium permanganate solution, and then washed with water and dried;

[0110] S02: ball milling the dried nano-hydroxyapatite and the effector according to a weight ratio of 5:3, with a ball milling speed of 1500r / min for 2h. After the ball milling is completed, washing and drying are performed to obtain the effector adjusted by the nano-hydroxyapatite;

[0111] S03: Preparation of continuous adjustment solution;

[0112] The preparation method of the continuous adjustment solution is:

[0113] 7 parts of silane coupling agent KH560, 3 parts of chitosan solution, 10 parts of sodium lignin sulfonate solution and 5 parts of ethanol solvent were mixed to obtain a continuous adjustment solution;

[0114] S04: the nano-hydroxyapatite-adjusted effect agent and the coupling liquid are mixed thoroughly in a weight ratio of 2:5 to obtain a coupling effect liquid;

[0115] S3: subjecting the heat-insulated flaky talcum powder and the coupling liquid to ultrasonic modification treatment in a weight ratio of 2:7. After the ultrasonic modification is completed, washing with water and drying are performed.

[0116] The ultrasonic power of the S3 ultrasonic modification treatment in this embodiment is 400 W, and the ultrasonic time is 30 min.

[0117] The mass fraction of the chitosan solution in S03 of this embodiment is 7%; the mass fraction of the sodium lignin sulfonate solution is 15%.

[0118] The preparation method of the effect-enhancing agent of the present embodiment is:

[0119] 3 parts of nano-silica sol and 4 parts of sodium dodecylbenzene sulfonate were added into 8 parts of 5% by mass yttrium nitrate solution, and then 3 parts of wollastonite and 2 parts of sodium citrate solution were added and stirred thoroughly to obtain an effective agent.

[0120] The mass fraction of the sodium citrate solution in this embodiment is 15%.

[0121] The preparation method of the nano silicon carbide modifier of this embodiment is:

[0122] S101: placing the nano-silicon carbide in a proton irradiation box for irradiation for 30 minutes at an irradiation power of 400 W, and obtaining a nano-irradiated silicon carbide agent after the irradiation is completed;

[0123] S102: 7 parts of nano-irradiated silicon carbide agent, 3 parts of tetrabutyl titanate, 2 parts of urea and 10 parts of lanthanum chloride solution are mixed and ball-milled at a ball-milling speed of 1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a nano-silicon carbide modifier.

[0124] The mass fraction of the lanthanum chloride solution in this embodiment is 5%.

[0125] A method for preparing an acid corrosion resistant insulating synthetic mica coating substrate according to the present embodiment comprises the following steps:

[0126] The raw materials are weighed according to the ratio; then the raw materials are sent to a mixer and mixed thoroughly, and then extruded in a twin-screw extruder at an extrusion temperature of 120° C., and then cooled to obtain a sheet material, and finally ground to a particle size of 400 meshes to obtain the acid-corrosion-resistant insulating synthetic mica coating substrate of the present invention.

[0127] Example 3.

[0128] The present embodiment provides an acid-corrosion-resistant insulating synthetic mica coating substrate, the coating substrate comprising the following raw materials in parts by weight:

[0129] 17.5 parts of synthetic mica powder, 11 parts of coupling effect double adjuster, 5.5 parts of nano silicon carbide modifier, 35 parts of epoxy resin, 7.5 parts of curing agent, 3 parts of polydimethylsiloxane, 0.75 parts of benzoin;

[0130] Synthetic mica powder is made by wet crushing and grinding process:

[0131] The synthetic mica fragments were sorted and soaked, crushed by 5.0MPa high-pressure water impact, dehydrated, crushed by a wheel mill with a gap of 0.9mm, classified and dried to obtain synthetic mica powder with a particle size of 400 mesh.

[0132] The epoxy resin in this embodiment is a phenolic modified epoxy resin, the epoxy value is 0.13eq / 100g, and the softening point is 115°C; the curing agent is a phenolic curing agent, and the phenolic curing agent is p-diphenol.

[0133] The preparation method of the coupling effect double regulator of this embodiment is:

[0134] The specific preparation method is:

[0135] S1: The flaky talc was first heat treated at 315°C for 12.5 min, then the temperature was reduced to 180°C at a rate of 3.5°C / min, and kept at this temperature for 7.5 min, and finally the temperature was reduced to 55°C at a rate of 2°C / min, and kept at this temperature;

[0136] S2: Preparation of coupling liquid;

[0137] The specific preparation method is:

[0138] S01: First, the nano-hydroxyapatite is stirred and mixed in a sufficient amount of 10% by mass potassium permanganate solution, and then washed with water and dried;

[0139] S02: ball milling the dried nano-hydroxyapatite and the effector according to a weight ratio of 5:3, with a ball milling speed of 1250r / min for 1.5h. After the ball milling is completed, washing and drying are performed to obtain the effector adjusted by the nano-hydroxyapatite;

[0140] S03: Preparation of continuous adjustment solution;

[0141] The preparation method of the continuous adjustment solution is:

[0142] 5.5 parts of silane coupling agent KH560, 2 parts of chitosan solution, 8 parts of sodium lignin sulfonate solution and 4 parts of ethanol solvent were mixed to obtain a continuous adjustment solution;

[0143] S04: the nano-hydroxyapatite-adjusted effect agent and the coupling liquid are mixed thoroughly in a weight ratio of 2:5 to obtain a coupling effect liquid;

[0144] S3: subjecting the heat-insulated flaky talcum powder and the coupling liquid to ultrasonic modification treatment in a weight ratio of 1:3, washing with water and drying after the ultrasonic modification.

[0145] The ultrasonic power of S3 in the ultrasonic modification treatment of this embodiment is 370W, and the ultrasonic time is 25min.

[0146] The mass fraction of the chitosan solution in S03 of this embodiment is 5.5%; the mass fraction of the sodium lignin sulfonate solution is 12.5%.

[0147] The preparation method of the effect-enhancing agent of the present embodiment is:

[0148] 2 parts of nano-silica sol and 3.5 parts of sodium dodecylbenzene sulfonate were added to 6.5 parts of 5% by mass yttrium nitrate solution, and then 2.5 parts of wollastonite and 1.5 parts of sodium citrate solution were added and stirred thoroughly to obtain an enhancer.

[0149] The mass fraction of the sodium citrate solution in this embodiment is 12.5%.

[0150] The preparation method of the nano silicon carbide modifier of this embodiment is:

[0151] S101: placing the nano-silicon carbide in a proton irradiation box for 25 minutes, with an irradiation power of 370W, and obtaining a nano-irradiated silicon carbide agent after the irradiation is completed;

[0152] S102: 5.5 parts of nano-irradiated silicon carbide agent, 2 parts of tetrabutyl titanate, 1.5 parts of urea and 8 parts of lanthanum chloride solution are mixed and ball-milled at a ball-milling speed of 1250 r / min for 1.5 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a nano-silicon carbide modifier.

[0153] The mass fraction of the lanthanum chloride solution in this embodiment is 3%.

[0154] A method for preparing an acid corrosion resistant insulating synthetic mica coating substrate according to the present embodiment comprises the following steps:

[0155] The raw materials are weighed according to the ratio; then the raw materials are sent to a mixer and mixed thoroughly, and then extruded in a twin-screw extruder at an extrusion temperature of 120° C., and then cooled to obtain a sheet material, and finally ground to a particle size of 400 meshes to obtain the acid-corrosion-resistant insulating synthetic mica coating substrate of the present invention.

[0156] Comparative Example 1.

[0157] The difference from Example 3 is that no coupling effect double adjuster is added.

[0158] Comparative Example 2.

[0159] The difference from Example 3 is that the S1 step is not used in the preparation of the coupling effect double regulator.

[0160] Comparative Example 3.

[0161] The difference from Example 3 is that no coupling effect liquid treatment is used in the preparation of the coupling effect double adjustment.

[0162] Comparative Example 4.

[0163] The difference from Example 3 is that no dry nano-hydroxyapatite is added to the coupling liquid.

[0164] Comparative Example 5.

[0165] The difference from Example 3 is that no effector is used in the coupling liquid.

[0166] Comparative Example 6.

[0167] The difference from Example 3 is that the coupling agent in the coupling liquid is replaced by ethanol solvent.

[0168] Comparative Example 7.

[0169] The difference from Example 3 is that no silane coupling agent KH560 or chitosan solution is added in the preparation of the continuous adjustment solution.

[0170] Comparative Example 8.

[0171] The difference from Example 3 is that no nano silicon carbide modifier is added.

[0172] Comparative Example 9.

[0173] The difference from Example 3 is that S102 treatment was not used in the preparation of the enhancement agent.

[0174] Comparative Example 10.

[0175] The difference from Example 3 is that tetrabutyl titanate and urea are not added in the S102 treatment.

[0176] The spraying technology of the products of Examples 1-3 and Comparative Examples 1-10 forms a 2mm coating. The anti-fouling and self-cleaning performance test is to coat the product coating with dirt and oil in a weight ratio of 2:1, and then place it at 40°C for 6 hours. Wipe the product and test the wiping force to wipe the dirt clean. The product is subjected to conventional performance tests. In addition, it is placed under 2% hydrochloric acid mist for 12 hours to test the acid corrosion resistance of the product. The performance measurement results are as follows

[0177]

[0178] It is concluded from Examples 1-3 and Comparative Examples 1-10 that

[0179] The product of Example 3 of the present invention can achieve coordinated improvement in breakdown voltage and wiping force under normal conditions, and the product has significant insulation and anti-fouling and self-cleaning properties. At the same time, the product has excellent performance stability under acid corrosion resistance conditions;

[0180] From Comparative Examples 1-7, Comparative Example 8 and Example 3, it can be seen that the product does not add a coupling effect double adjuster and does not add a nano silicon carbide modifier, and the performance of the product has a significant trend of deterioration. The performance effect is most significant when the two are coordinated.

[0181] It can be seen from Comparative Examples 2-7 and Example 3 that the S1 step is not used in the preparation of the coupling effect double adjustment, the coupling effect liquid is not used in the preparation of the coupling effect double adjustment, the dry nano-hydroxyapatite is not added to the coupling effect liquid, and the effect agent is not used in the coupling effect liquid. The performance of the product has a tendency to deteriorate. The effect agent is not used in the coupling effect liquid. The performance trend of the product changes more obviously. The effect agent treatment, the effect agent treatment and the S1 step treatment of the present invention are used. The performance effect of the product is the most obvious;

[0182] The coupling effect liquid was replaced by ethanol solvent, and the silane coupling agent KH560 and chitosan solution were not added in the preparation of the liquid. The performance of the product showed a trend of deterioration. The liquid prepared by the raw materials of the present invention had the most significant product performance effect.

[0183] It can be seen from Comparative Examples 8-10 and Example 3 that the performance of the products tended to deteriorate when S102 treatment was not used in the preparation of the enhancement agent and tetrabutyl titanate and urea were not added in the S102 treatment. The performance effect of the product was most significant when the specific S102 treatment of the present invention was used.

[0184] From the above performance tests, it is found that the performance enhancer of the present invention has a significant effect on the performance of the product, and further research is conducted on this:

[0185] The preparation method of the effect-enhancing agent is:

[0186] 2 parts of nano-silica sol and 3.5 parts of sodium dodecylbenzene sulfonate are added to 6.5 parts of yttrium nitrate solution with a mass fraction of 5%, and then 2.5 parts of wollastonite and 1.5 parts of sodium citrate solution are added and stirred thoroughly to obtain an effective agent; the mass fraction of the sodium citrate solution is 12.5%.

[0187] Experimental example 1.

[0188] The only difference from Example 3 is that no nano-silica sol is added in the preparation of the enhancement agent.

[0189] Experimental example 2.

[0190] The only difference from Example 3 is that wollastonite is not added in the preparation of the enhancement agent.

[0191] Experimental Example 3.

[0192] The only difference from Example 3 is that deionized water is used instead of yttrium nitrate solution in the preparation of the enhancement agent.

[0193] Experimental Example 4.

[0194] The only difference from Example 3 is that no sodium citrate solution was added during the preparation of the enhancement agent.

[0195] Experimental Example 5.

[0196] The only difference from Example 3 is that sodium dodecylbenzene sulfonate is not added in the preparation of the enhancement agent.

[0197] Experimental Example 6.

[0198] The only difference from Example 3 is that the mass fraction of the sodium dodecylbenzene sulfonate solution in the preparation of the enhancement agent is 8%.

[0199]

[0200] It can be seen from Experimental Examples 1-6 that wollastonite was not added in the preparation of the effector, and the performance change trend of the product had the greatest impact on the preparation of the effector. The use of wollastonite had a significant improvement on the performance of the product. Deionized water was used instead of yttrium nitrate solution in the preparation of the effector, and the performance of the product also showed a more obvious deterioration trend. At the same time, no nano-silica sol was added in the preparation of the effector, no sodium citrate solution was added in the preparation of the effector, no sodium dodecylbenzene sulfonate was added, and the mass fraction of the sodium dodecylbenzene sulfonate solution was 8%, and the performance of the product showed a deterioration trend. The effector obtained by the preparation method of the present invention has the most significant performance effect of the product, and the effects of other methods are not as significant as those of the present invention.

[0201] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0202] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. An acid corrosion resistant insulating synthetic mica coating substrate, characterized in that: The coating substrate comprises the following raw materials in parts by weight: 15-20 parts of synthetic mica powder, 8-14 parts of coupling effect double adjuster, 4-7 parts of nano silicon carbide modifier, 30-40 parts of epoxy resin, 6-9 parts of curing agent, 2-4 parts of polydimethylsiloxane, 0.5-1.0 parts of benzoin; The synthetic mica powder is made by wet crushing and grinding process: The synthetic mica fragments are sorted and soaked, crushed by 4.0-7.0MPa high-pressure water impact, dehydrated, crushed by a wheel mill with a gap of 0.8-1mm, classified, and dried to obtain synthetic mica powder with a particle size of 400 mesh; The preparation method of the coupling effect double regulator is: The specific preparation method is: S1: first heat-treat the flaky talc at 310-320°C for 10-15 min, then reduce the temperature to 175-185°C at a rate of 2-5°C / min, keep the temperature for 5-10 min, and finally reduce the temperature to 55°C at a rate of 1-3°C / min, and keep the temperature; S2: Preparation of coupling liquid; The specific preparation method is: S01: First, the nano-hydroxyapatite is stirred and mixed in a sufficient amount of 10% by mass potassium permanganate solution, and then washed with water and dried; S02: ball milling the dried nano-hydroxyapatite and the effector according to a weight ratio of 5:3, with a ball milling speed of 1000-1500 r / min for 1-2 hours. After the ball milling is completed, washing and drying are performed to obtain the effector adjusted by the nano-hydroxyapatite; S03: Preparation of continuous adjustment solution; The preparation method of the continuous adjustment solution is: 4-7 parts of silane coupling agent KH560, 1-3 parts of chitosan solution, 6-10 parts of sodium lignin sulfonate solution and 3-5 parts of ethanol solvent are mixed to obtain a continuous adjustment solution; S04: the nano-hydroxyapatite-adjusted effect agent and the coupling liquid are mixed thoroughly in a weight ratio of 2:5 to obtain a coupling effect liquid; S3: subjecting the heat-insulated flaky talc powder and the coupling liquid to ultrasonic modification in a weight ratio of 2:(5-7), washing with water and drying after the ultrasonic modification; The preparation method of the effect-enhancing agent is: 1-3 parts of nano silica sol and 3-4 parts of sodium dodecylbenzene sulfonate are added to 5-8 parts of 5% by mass yttrium nitrate solution, and then 2-3 parts of wollastonite and 1-2 parts of sodium citrate solution are added and stirred to obtain an effective agent; The preparation method of the nano silicon carbide modifier is: S101: placing the nano-silicon carbide in a proton irradiation box for irradiation for 20 to 30 minutes, with an irradiation power of 350 to 400 W, and obtaining a nano-irradiated silicon carbide agent after the irradiation is completed; S102: 4 to 7 parts of nano-irradiated silicon carbide agent, 1 to 3 parts of tetrabutyl titanate, 1 to 2 parts of urea and 6 to 10 parts of lanthanum chloride solution are mixed and ball-milled at a speed of 1000 to 1500 r / min for 1 to 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a nano-silicon carbide modifier.

2. The acid corrosion resistant insulating synthetic mica coating substrate according to claim 1, characterized in that: The epoxy resin is a phenolic modified epoxy resin, the epoxy value is 0.12-0.135eq / 100g, and the softening point is 110-120°C; the curing agent is a phenolic curing agent, and the phenolic curing agent is p-diphenol.

3. The acid corrosion resistant insulating synthetic mica coating substrate according to claim 1, characterized in that: The ultrasonic power of the ultrasonic modification treatment in S3 is 350-400W, and the ultrasonic time is 20-30min.

4. The acid corrosion resistant insulating synthetic mica coating substrate according to claim 1, characterized in that: The mass fraction of the chitosan solution in the S03 is 4-7%; the mass fraction of the sodium lignin sulfonate solution is 10-15%.

5. The acid corrosion resistant insulating synthetic mica coating substrate according to claim 1, characterized in that: The mass fraction of the sodium citrate solution is 10-15%.

6. The acid corrosion resistant insulating synthetic mica coating substrate according to claim 1, characterized in that: The mass fraction of the lanthanum chloride solution is 2-5%.

7. A method for preparing an acid corrosion resistant insulating synthetic mica coating substrate as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: The raw materials are weighed according to the ratio; then the raw materials are sent to a mixer for thorough mixing, and then extruded in a twin-screw extruder at an extrusion temperature of 120° C., and then cooled to obtain a sheet material, and finally ground to a particle size of 400 meshes to obtain an acid-resistant insulating synthetic mica coating substrate.

Citation Information

Patent Citations

  • Anti-corrosive coating for surface layer of electrical equipment and preparation method ofanti-corrosive coating

    CN108395785A

  • Self-adhesive paint for transposed conductor and coating method of self-adhesive paint

    CN117264498A